Prognostic Values of Long Noncoding RNA GAS5 in Various Carcinomas: An Updated Systematic Review and Meta-Analysis - Gao, Qunjun; Xie, Haibiao; Zhan, Hengji; Li, Jianfa; Liu, Yuchen; Huang, Weiren (Frontiers in Physiology, 2017)
The growth arrest-specific transcript 5 (GAS5) is a long noncoding RNA with low expression in multiple cancers. This meta-analysis aims to explore the association between GAS5 expression levels and cancer patients' prognosis. We collected all the relevant literatures about GAS5 expression levels associated with overall survival (OS), lymph node metastasis (LNM) and high tumor stage (II/III/IV) (HTS) from the PubMed and Web of Science. The hazard ratio (HR) and the corresponding 95% confidence interval (CI) were calculated to evaluate the link strength between GAS5 and cancer prognosis. A total of 934 patients from 14 studies were included to the present meta-analysis, according to the inclusion and exclusion criteria. The results demonstrated that low expression of GAS5 could predict poor OS in cancer patients (HR=1.955, 95%CI: 1.551-2.465, P<0.001). Meanwhile we also analyzed the following cancers independently: hepatocellular carcinoma (HR=1.893, 95% CI: 1.103-3.249, P=0.021) and urothelial carcinoma (HR=1.653, 95% CI: 1.185-2.306, P=0.003). Compared to the high GAS5 expression group, additionally, patients with low GAS5 expression in tumor tissues were more prone to lymph node metastasis (OR=0.234, 95 %CI: 0.153-0.358, P<0.001) and high tumor stage (OR=0.185 (95 %CI:0.102-0.333, P<0.001). In conclusion, this meta-analysis showed that GAS5 might be served as a novel biomarker for predicting prognosis in various types of cancers.